Study of the Effect of Adding Eco-Enzyme to the Process of Decomposing Organic Waste on the Quality of Compost, Leachate, and Methane Gas Production - Anik Sarminingsih; Sri Sumiyati; Syafrudin Syafrudin; Irfan Alfarisi; Risky Setiawan; Axelino Farrell Andika; Mustika Balqis (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Waste generation is increasing along with the increase in population and human living needs. The most dominant waste composition in Indonesia is organic waste, which accounts for 53.97% of the total waste. Eco-enzyme is one of the waste utilization products that has the potential to become an activator for the decomposition process and reduce the environmental effects of waste decomposition. The aim of this research is to analyse the micronutrient content of compost, reduce leachate toxicity, and accelerate the production of methane gas resulting from decomposition using eco-enzymes. The method used was an experimental method (trial) to obtain primary data from laboratory test results during 28 days of research. The research results show that, in general, there is a significant difference in the quality of compost in organic waste that uses eco-enzyme compared to that that does not use eco-enzyme. The results of measuring the quality of the leachate resulting from decomposition show that the quality of the leachate that uses eco-enzyme is better and has lower toxicity than without using eco-enzyme (control). In the production of methane gas, the results show that methane gas production in decomposition using eco-enzymes reaches the methanogenesis process more quickly.